PENGEMBANGAN FRONT END SISTEM INFORMASI MANAJEMEN ABSENSI PEGAWAI AVATAR SOLUTIONS - Anggara Putra, I Wayan Aditya; Arya Kadyanan, I Gusti Agung Gede (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
The development of technology in the field of information and communication in this era is developing so fast. With all the ease of accessing the internet the impact on the web program is very helpful in completing work that was still manual. Avatar Solutions is a company that focuses on comprehensive web-based information management solutions coupled with complete hardware and software packages and reliable technical support. Avatar Solutions has an organizational structure that will move as a team to achieve the company's vision and mission. With an organizational structure such as a good attendance system is needed to regulate work time and rest periods per day from employees. Because of the reasons above, the author made the Front End Attendance Management Information System Employee Development aimed at helping employees to attend attendance efficiently. Through this system, it is expected that the employees will be facilitated in carrying out the attendance process through a web-based system.